(untitled) (Sains Humanika, 2021)
This paper is to identify the mainstreams that are associated with performance management research in the HR and other fields to give clear guidance for future study that will give guidance for performance management research by further studying the PM mainstream that will then contribute to business and academic field. The research is done by conducting systematic literature review of several current papers discussing variety aspects of performance management practices in HR and other fields, by limiting only on the current mainstreams. Based on that limitation, this paper does not discuss either the relationship between the mainstreams or the effects of an existence of PMS on performance of a company. From the research it is found that there are several mainstreams on performance management based on current papers and it also noted that good performance of a company is not necessarily a result from an implementation of a Performance Management System (PMS) but just good practices of human resources, knowledge management and others. Further studies can be done to analyze the relationships between the mainstreams and find methodologies to develop effective models of PMS considering the features and studied mainstreams.It also can study the basic effectiveness of PMS implementation compared to using other toolsets such as knowledge management.Â